Performance of static MDCT beam-shaping filtration for elliptical subject geometries in dependence of projection angle - Veloza, LS; Kauczor, HU; Stiller, W (RöFo : Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebende Verfahren, 2011)
Ziele: MDCT beam-shaping filters modulate X-ray beam intensity across the fan, compensating for decreasing absorption due to shorter X-ray path lengths through patient body periphery compared to its center. To investigate projection-angle dependence of detector statistics for elliptical subject geometries, performance of experimentally measured filter geometry and theoretical filter geometry adapted to elliptical specimen has been compared. Methode: Using a Compton spectrometer, primary MDCT X-ray spectra (120kVp) have been measured at different angular distance (0°–21°) from the central ray of the X-ray fan. These have been used to calculate the geometrical shape of the aluminum bowtie filter. A theoretical filter model was determined for elliptical subject geometries. For both shape models, detector statistics after X-ray passage through a homogeneous elliptical phantom (16.0cm semimajor axis, 12.5cm semiminor axis, 8.0cm thickness) of polypropylene, PMMA and water was Monte-Carlo simulated with Geant4. The number of surviving quanta after X-ray passage through beam-shaping filter plus phantom was counted by a detector array positioned for projections a.p. to lateral in 15°-steps. Ergebnis: At the fan edge, measured filter shape is systematically too thin: for lateral projections maximum difference is 28% compared to the theoretical filter model for elliptical subject geometries. Performance of the latter varies with projection angle and thus requires adaption of geometry to view angle. Schlussfolgerung: Static beam-shaping filter geometry and its material composition should be reevaluated to reduce signal and thus patients' skin dose for lateral projections. Dynamic beam-shaping concepts could allow for radiation exposure reduction in MDCT. Keywords: bowtie filter, Monte Carlo simulation, computed tomography, Geant4 simulation, beam filtration Korrespondierender Autor: Veloza LS UniveristätsKlinikum Heidelberg, Diagnostische und Interventionelle Radiologie, Im Neuenheimer Feld 110, 69120 Heidelberg E-Mail: stella.veloza@med.uni-heidelberg.de